2008
DOI: 10.1007/s11431-008-0223-5
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature oxidation behavior of Al2O3/TiAl matrix composite in air

Abstract: The oxidation behavior of Al 2 O 3 /TiAl in situ composites fabricated by hot-pressing technology was investigated at 900℃ in static air. The results indicate that the mass gains of the composites samples decrease gradually with increasing Nb 2 O 5 content and the inert Al 2 O 3 dispersoids effectively increase the oxidation resistance of the composites. The higher the Al 2 O 3 dispersoids content, the more pronounced the effect. The primary oxidation precesses obey approximately the linear laws, and the cycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Similar phases in case of plasma sprayed Al 2 O 3 –TiO 2 coating has been reported by Gok. 20 According to Ai et al 24 TiO 2 phase forms along the splat boundaries and contact each other, and Al 2 O 3 phase forms inside the splats.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Similar phases in case of plasma sprayed Al 2 O 3 –TiO 2 coating has been reported by Gok. 20 According to Ai et al 24 TiO 2 phase forms along the splat boundaries and contact each other, and Al 2 O 3 phase forms inside the splats.…”
Section: Resultsmentioning
confidence: 98%
“…The intact phases might be of Al 2 O 3 and Al 2 O 3 –TiO 2 phases, which remained adherent on the surface. According to Ai et al 24 the multi-structure of the TiO 2 –Al 2 O 3 mixed layer decreases the diffusion of oxygen ions inside the subsurface region of the coating thus improving the high temperature oxidation resistance. They further suggested that the continuous protective alumina scales do not form on the surface of oxidation scales.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their working temperature can reach 750–900 °C, which is close to that of the widely used Ni-based alloys, but the density is only half of the latter. Therefore, TiAl-based alloys have the potential to replace Ni-based alloys as aerospace structural components and transmission parts of power systems, which can greatly improve the thrust-weight ratio and fuel efficiency of the engines [1,2,3,4,5]. However, the intrinsic brittleness results in poor processing performance; thus, it hinders their further applications.…”
Section: Introductionmentioning
confidence: 99%
“…Intermetallic matrix composites (IMCs) can provide the right combination of HighTemperature strength and creep resistance and overcome the problem of poor ductility and toughness at ambient temperature [9]. Compounds such as Al 2 O 3 , TiB 2 , Ti 5 Si 3 , and Ti 2 AlC have been previously identified as compatible and thermochemically stable reinforcements for TiAl intermetallics [4,[10][11][12][13][14][15][16][17][18]. However, much more attention has been given to Ti 2 AlC reinforcement [11,17,18].…”
Section: Introductionmentioning
confidence: 99%